Trust: a determinant or the consequence of a long-term buyer-seller relationship. - Batt, Peter (International Society for Horticultural Science, 2000)
Satisfaction with the relationship between Filipino potato farmers and their preferred seed supplier is derived from the seed supplier's offer quality and the extent to which investments made by the seed supplier support and assist the farmer. However, while satisfaction leads to trust, the relationship between trust and the farmer's long-term commitment to the relationship is more tenuous. These relationship specific investments have a direct impact on the farmer's desire to maintain a long-term relationship which, in turn, results in greater trust between the farmer and their most preferred seed supplier. Whereas the majority of authors conceptualise trust as a determinant of a long-term buyer-seller relationship, it would appear, at least in this study, that trust between potato farmer's and their most preferred seed supplier is the principal outcome of the relationship.